REGISTRATION MECHANISM OF BRAND RIGHTS ON THE CV. TRIBINA JASAINDO (PRACTICAL WORK AT CV. TRIBINA JASAINDO) - Indry Wulandari Irawan; Winsherly Tan (Universitas Internasional Batam, 2022)
A brand is something that is used to get to know a product or company in commerce. Brand rights are also one of the components of intellectual property that align with copyright, patents, and other intellectual property rights. Registering a brand can avoid unfair business competition. For people who live in small towns and do not understand the rules of the brand, it is rare to register a brand even though the resulting product is conventional in wide circles. Brand registration is considered quite difficult and can only be registered in certain places, namely at the Office of the Director General of IPR Jakarta or through the DepkumHAM Kanwil in the provincial capital, therefore being one of the factors in the least number of brand registrations in Indonesia. Riau Islands Province. Related to these problems, the place used to conduct research is to carry out practical work on the CV. Tribina Jasaindo is a business entity engaged in document management services in Batam City. This research uses normative legal methods based on literature studies, then delivered through design ideas in accordance with the working title of practice and data information processing to perform designs on a series of activities. The results of this study show that the procedures for brand registration and its protection are regulated in Law No. 15 of 2001 on Brands.